العتبات الحرارية الحرجة وساعات البرودة لأشجار الفاكهة دراسة في المناخ التطبيقي (Comprehensive Journal of Science, 2025)
This research analyzes the dialectical relationship between the physiological requirements of fruit trees and the thermal thresholds that determine their growth and productivity, particularly in light of the challenges posed by climate extremes. The study aims to identify the "thermal safety margin" for various horticultural species—including palms, citrus, and deciduous trees—and to determine thermal sensitivity levels during critical growth stages. Adopting a comparative analytical approach, the research relies on climatic and physiological data from Iraq and Jordan spanning the period (1955-2011), supplemented by a review of recent studies (2021-2024).The findings reveal a wide variation in the trees' ability to withstand heat stress; date palms emerged as the most tolerant species, with an optimal threshold reaching 44°C, while deciduous varieties such as almonds and apples showed extreme sensitivity to high temperatures. Regarding lower thresholds, the research proves that the "climatic point of weakness" lies in the flowering and fruit-setting stages, where tissue resistance to spring frost collapses, causing damage at temperatures near freezing (-0.6°C to -2°C), despite the same trees enduring harsh winter freezing during their dormancy period. The results also emphasize the importance of fulfilling cumulative chilling hours for foreign varieties (e.g., McIntosh and Roma apples) to ensure the breaking of dormancy.The research concludes that the temporal synchronization between thermal conditions and growth stages is the decisive factor in production stability. It recommends the adoption of thermal suitability maps when selecting varieties and the implementation of field protection techniques, such as windbreaks—which have proven effective in doubling productivity. Furthermore, it suggests a shift toward breeding strains whose chilling requirements align with current global warming trends.